(untitled) (Lundiana: International Journal of Biodiversity, 2002)
Anniversaries and commemorations often inspire us to tell stories about a person’s life as if it was the staging of a final scene – the achievement or frustration of ambition – a final scene that allows us to understand a person’s life as part of history, and history as if it was based on the life of its characters. In contemporary historiography it is recognized that history can never be reduced solely to a report about its heroes and that the life of a person rarely confounds itself only with a person’s work and ambitions. [Continues]